Characterising Interactions Between Amyloid-beta 42 and Amylin Peptide Heterodimers: A Molecular Simulation Approach - Sonar, Krushna Satish (Curtin University, 2022)
Amyloid-beta 42 (Aß42) and amylin are intrinsically disordered peptides. Pathogenic aggregation of peptides results in Alzheimer’s disease (AD) and Type-2 diabetes (T2D), by Aß42 and amylin, respectively. High risk of AD in T2D patients exists due to cross-aggregation in brain. Difficulty in in-vitro characterisation aggregation mechanism elusive. We have managed to shed light on mechanism by sampling conformations and exploiting the hydrophobic nature of peptides using enhanced simulation on monomer (Aß42), Aß42 homo-and heterodimer (Aß42-Amylin).